Comparison of postoperative outcomes among patients treated by male and female surgeons: a population based matched cohort study. (10th October 2017) - Wallis, Christopher JD; Ravi, Bheeshma; Coburn, Natalie; Nam, Robert K; Detsky, Allan S; Satkunasivam, Raj
Abstract : Objective  To examine the effect of surgeon sex on postoperative outcomes of patients undergoing common surgical procedures. Design  Population based, retrospective, matched cohort study from 2007 to 2015. Setting  Population based cohort of all patients treated in Ontario, Canada. Participants  Patients undergoing one of 25 surgical procedures performed by a female surgeon were matched by patient age, patient sex, comorbidity, surgeon volume, surgeon age, and hospital to patients undergoing the same operation by a male surgeon. Interventions  Sex of treating surgeon. Main outcome measure  The primary outcome was a composite of death, readmission, and complications. We compared outcomes between groups using generalised estimating equations. Results  104 630 patients were treated by 3314 surgeons, 774 female and 2540 male. Before matching, patients treated by female doctors were more likely to be female and younger but had similar comorbidity, income, rurality, and year of surgery. After matching, the groups were comparable. Fewer patients treated by female surgeons died, were readmitted to hospital, or had complications within 30 days (5810 of 52 315, 11.1%, 95% confidence interval 10.9% to 11.4%) than those treated by male surgeons (6046 of 52 315, 11.6%, 11.3% to 11.8%; adjusted odds ratio 0.96, 0.92 to 0.99, P=0.02). Patients treated by female surgeons were less likely to die within 30 days (adjusted odds ratio 0.88; 0.79 to 0.99, P=0.04), but there was no significant difference in readmissions or complications. Stratified analyses by patient, physician, and hospital characteristics did not significant modify the effect of surgeon sex on outcome. A retrospective analysis showed no difference in outcomes by surgeon sex in patients who had emergency surgery, where patients do not usually choose their surgeon. Conclusions  After accounting for patient, surgeon, and hospital characteristics, patients treated by female surgeons had a small but statistically significant decrease in 30 day mortality and similar surgical outcomes (length of stay, complications, and readmission), compared with those treated by male surgeons. These findings support the need for further examination of the surgical outcomes and mechanisms related to physicians and the underlying processes and patterns of care to improve mortality, complications, and readmissions for all patients.